Psychology of the Gender-Equitable Environment: Research of Problems - Kikinezhdi, Oksana M.; Zhyrska, Halyna Ya.; Chip, Ruslana S.; Vasylkevych, Yaroslava Z.; Hovorun, Tamara V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The purpose of our study was to perform a comparative analysis of the level characteristics of the subjective perception of the egalitarian psychological well-being of participants in the educational process in mono- and heterogender educational space. The study used qualitative and quantitative methods to measure the level of psychological safety and psychological protection of participants in the educational process. The study relied on a questionnaire that was adapted to identify three indicators: “integrated indicator of the attitude to the educational environment”, “significant characteristics of the educational environment and the index of satisfaction with it”, “index of psychological security of the educational environment”. A pilot project that was developed on the basis of the Research Centre for Gender Education and Development of Pupils and Students of the National Academy of Educational Sciences of Ukraine determined the educational vectors for building the psychology of an egalitarian safe, educational environment. The analysis found significant differences in the value of the coefficient of psychological well-being of participants in the educational process in all three models of organization of educational space. The masculine model revealed statistically significant signs of subjective psychological distress in cadets compared to the other two models. The satisfaction of parents and teachers with the level of psychological security in a gender-homogeneous educational environment is quite high. The model which reflects the feminine principle of forming study groups is subjectively perceived by students as psychologically safe.